2013
DOI: 10.1080/00380768.2013.822301
|View full text |Cite
|
Sign up to set email alerts
|

Red soils derived from limestone contain higher amounts of trace elements than those derived from various other parent materials

Abstract: The concentrations of 48 trace elements (Li, Be, Sc, V, Cr, Co, Ni, Cu, Zn, Ga, As, Br, Rb, Sr, Y, Zr, Nb, Mo, Ag, In, Cd, Sn, Sb, I, Cs, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, Ta, W, Tl, Pb, Bi, Th and U) in 14 soils derived from limestone, sampled at three sites, are compared with the concentrations in 500 soil samples derived from a variety of other parent materials. The 500 samples were collected from 75 sites nationwide in order to include the wide range of common soil types in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Summary statistics (mean, median, minimum: min, maximum: max. and range in mg/kg, standard deviation: SD and skewness: Skew) and Shapiro-Wilk test for Pb and Zn concentration in A and B horizon Kernel density plot of Pb A and Pb B (a) and Zn A and Zn B (b)Established elevated Pb concentrations in the current study are in agreement with those reported byBellanca et al (1996),Vingiani et al (2018) andYamasaki et al (2013) for Terra rossa soils on limestones(Table 3) Peh et al (2003). also have established very similar mean values of Pb in Terra rossa soil(Table 3).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Summary statistics (mean, median, minimum: min, maximum: max. and range in mg/kg, standard deviation: SD and skewness: Skew) and Shapiro-Wilk test for Pb and Zn concentration in A and B horizon Kernel density plot of Pb A and Pb B (a) and Zn A and Zn B (b)Established elevated Pb concentrations in the current study are in agreement with those reported byBellanca et al (1996),Vingiani et al (2018) andYamasaki et al (2013) for Terra rossa soils on limestones(Table 3) Peh et al (2003). also have established very similar mean values of Pb in Terra rossa soil(Table 3).…”
supporting
confidence: 90%
“…Original scientific paper DOI: /10.5513/JCEA01/21.3.2588 Miloš and Bensa: Lead and zinc concentration in genetic horizons of Terra rossa soil at a... Peh et al (2003), Bellanca et al (1996) and Vingiani et al (2018), Table 4. Yamasaki et al (2013) have reported a higher mean value and a wider range of Zn concentration in topsoil (Table 4)…”
Section: Statistical Analysis Of Pb and Zn Concentrationsmentioning
confidence: 96%
“…The natural presence of As in soils is primarily influenced by the composition of geological parent materials [13,14]. It has been shown that there is a strong correlation between As in soils in northwest Greece and geological parent materials and anthropogenic sources of pollution [4].…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of potentially toxic elements (PTEs) in agricultural lands has emerged as a global concern due to the growing recognition of the importance of safe food production. The karst areas in southwestern China have been known to have high geochemical background values of various PTEs (Cd, Hg, As, Cr, Pb, Zn, Ni and Cu) in soils [1][2][3][4][5]. The high geochemical background of PTEs in these areas is related to the local carbonate rock parent materials [6].…”
Section: Introductionmentioning
confidence: 99%